Bahasa Inggris - Riani, Sri; Kasih, Apfia Mutiara; Raufanda, Miftakhul Sefti (Universitas Pendidikan Ganesha, 2024)
Environmental pollution by heavy metals is a crucial environmental problem and is a challenge to achieving the ideals of sustainable development. Blood cockles include Benthos from the Bivalvia Class Mollusk Phylum which has a wide habitat distribution in Indonesia. Beaches are very vulnerable to the accumulation of household waste, both from land and from the sea. Meanwhile, it has become an important part of economic, industrial and transportation growth in Surabaya. The aim of this research is to determine the comparison of the amounts of the heavy metals Lead (Pb), Ferrum (Fe), and Zinc (Zn) in blood cockles in two locations with different environmental characteristics and to evaluate whether the heavy metal content is still within the standard food threshold limit. The method used in this research is descriptive research with a survey method. Data analysis used correlation tests and independent sample t-tests. The research results show that the values of Lead (Pb) and Zinc (Zn) are higher in Lamong Bay, respectively, namely 0.00448 ± 0.0004 and 0.002 ± 0.0002. Meanwhile, the Ferrum (Fe) value is higher at Kenjeran Beach, namely 0.00284 ± 0.0006. The implications of this research can provide an overview of the level of heavy metal pollution in coastal ecosystems, which is important for monitoring the health of the aquatic environment. Heavy metals such as lead, iron and zinc have the potential to pose a threat to ecosystem balance and human health, especially if contaminated shellfish are consumed directly.